MAPPING OF PROSPECTIVE TEACHERS' INTEREST IN THE STUDY OF PANCASILA AND CITIZENSHIP EDUCATION BASED ON STUDY PROGRAM: ANALYSIS OF ARTICLE TITLE CHOICE - Maulia Depriya Kembara (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The study of Pancasila and Citizenship Education (PPKn) has an important role in shaping the character of students as active and responsible citizens. However, students' interest in this study may vary depending on their course of study and academic background. This study aims to analyze the tendency of students of Universitas Pendidikan Indonesia to the theme of PPKn based on the title of the article they choose. The data used came from a collection of student article titles that were analyzed using quantitative and qualitative approaches with text analysis techniques and keyword frequency mapping. The results showed that students from language and culture-based study programs (PBS & PBK) had the highest interest in PPKn, while fine arts students (PSR) had the lowest interest. The implications of these findings show the need for a more contextual and interactive PPKn learning approach to be more relevant for students from various study programs.